Integrasi Permainan Modern Tradisional Dan Islami Menggunakan Spinning Sebumbun Bagi Anak Usia Dini - Nur Aida; Neela Afifah; Saudah Saudah; Sri Hidayati; Liza Satiah; Baronisa Diana Putri (Pakis Journal Institute, 2024)
Early childhood education is education that applies strategies or methods of playing while learning, because the world of children is the world of play. At the time of learning it is very appropriate to use a media game, because the media can be a driving factor for students. Sebumbun spinning is one of the media that can improve aspects of development in children, with this media it will increase the enthusiasm and motivation to learn in children. The purpose of this community service is to provide knowledge and innovation to Al-Firdaus Palangka Raya Kindergarten teachers. The results of community service run smoothly where children are able to follow the rules of the game that have been determined before the game is carried out, and the enthusiasm of children when practicing games on Spinning Sebumbun media is very good, the hope is that learning with Spinning Sebumbun game media can be applied to schools other schools when learning takes place.